Hollywood holdup - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2006)
Bryce and Ashley Timberline volunteer to house-sit for some friends; however, as soon as they move in, strange things involving their neighbors begin to happen.
5.4
3-6
Keywords: Christian life -- Fiction; Halloween -- Fiction; Mystery and detective stories; Pet sitting -- Fiction; Stealing -- Fiction; Twins -- Fiction; Christian life -- Fiction; Halloween -- Fiction; Mystery fiction; Pet sitting -- Fiction; Theft -- Fiction; Twins -- Fiction; Colorado -- Fiction; Colorado -- Fiction